The role of personality traits and moral disengagement in academic dishonesty: An analysis of the big five and the dark tetrad - Julia Sánchez-García; Jorge Cebrián; Elena Fernández-del-Río; Pedro J. Ramos-Villagrasa (PLoS ONE, 2026)
Academic dishonesty – the inclination to cheat, falsify and plagiarise in the academic environment – is a growing concern in society, influenced by multiple psychological factors. This study aims to examine the role of personality traits (Big Five and Dark Tetrad) in academic dishonesty and exploratory analyses of potential mediating mechanisms, including of moral disengagement, in these relationships. A sample of 175 undergraduate students ( M age = 21.88 years, SD age = 5.23) completed self-report measures, including traditional and gamified personality assessments. Results showed that extraversion, openness to experience, and responsibility traits (gamified measure) were negatively associated with academic dishonesty, while neuroticism and Dark Tetrad traits were positively related to academic dishonesty. Exploratory mediation analyses suggested that lack of moral disengagement may play a role in these personality-dishonesty relationships. These results highlight the psychological mechanisms underlying academic dishonesty behaviours, emphasising the need to examine personality not only through traditional measures, but through gamified assessments in the age of emerging technologies. Interventions targeting moral disengagement warrant further investigation.